Case Report: Successful treatment with methotrexate in a 10-year-old boy with co-occurrence of generalized psoriasis and vitiligo - Leong, Pui-Ying; Chiu, Tsu-Man; Wei, James Cheng-Chung; Huo, An-Ping (Frontiers in Immunology, 2023)
The co-occurrence of psoriasis (PsO) and vitiligo is rare in Asian countries, especially in children. This case report presents the first-ever occurrence of PsO combined with vitiligo in an Asian boy under 6 years of age, in whom symptom improvement was observed after the use of methotrexate (MTX) as the sole treatment. Although previous studies have indicated that there is a close correlation between the two diseases, methotrexate (MTX), which is a commonly used treatment for PsO, is not a standard treatment for vitiligo. Even with advanced progress in biologics and Janus kinase inhibitor (JAKi), the biologics and JAKi used in vitiligo are still inconsistent. In our case report, the successful use of MTX indicated that there are shared immune pathways between PsO and vitiligo. Further exploration is needed to optimize the treatment options for this co-occurrence of PsO and vitiligo.